2012
DOI: 10.3389/fnhum.2012.00312
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interbrain synchronization and network properties when playing guitar in duets

Abstract: To further test and explore the hypothesis that synchronous oscillatory brain activity supports interpersonally coordinated behavior during dyadic music performance, we simultaneously recorded the electroencephalogram (EEG) from the brains of each of 12 guitar duets repeatedly playing a modified Rondo in two voices by C.G. Scheidler. Indicators of phase locking and of within-brain and between-brain phase coherence were obtained from complex time-frequency signals based on the Gabor transform. Analyses were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
274
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(299 citation statements)
references
References 55 publications
(84 reference statements)
23
274
0
2
Order By: Relevance
“…These results also confirmed previous findings (26)(27)(28)34) that neural activity (as well as interactive communication behaviors) could be used to differentiate reliably the leaders from the followers. It is worth noting that different studies have found different earliest time points for successful discrimination based on neural activity: before the onset of the interactions in Sänger et al (26,27) and Konvalinka et al (34) and about half a minute into the interaction in our study. One possible explanation of these variations is that the time point for successful discrimination depends on how the leaders emerge.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results also confirmed previous findings (26)(27)(28)34) that neural activity (as well as interactive communication behaviors) could be used to differentiate reliably the leaders from the followers. It is worth noting that different studies have found different earliest time points for successful discrimination based on neural activity: before the onset of the interactions in Sänger et al (26,27) and Konvalinka et al (34) and about half a minute into the interaction in our study. One possible explanation of these variations is that the time point for successful discrimination depends on how the leaders emerge.…”
Section: Discussionsupporting
confidence: 90%
“…One possible explanation of these variations is that the time point for successful discrimination depends on how the leaders emerge. In Sänger et al (26,27), leaders were assigned a priori; in Konvalinka et al (34), leaders emerged through a number of repeated trials; and, in the present study, leaders emerged during a single LGD task. Future research should specifically examine the role of neural activity or INS in predicting different types of leader emergence.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Socially interactive tasks requiring temporal coordination are also associated with large pools of neurons oscillating coherently across co-acting individuals' brains. This phenomenon has been observed in dual-EEG studies employing diverse tasks requiring joint rhythmic behaviour, such as guitar duet performance [75][76][77], unconscious imitation of finger movements [78], explicit imitation of hand movements [79] and joint speech [80]. Dual-EEG set-ups provide a promising avenue for exploring the temporal dynamics of mechanisms supporting rhythmic joint action, though the complexity of such set-ups means that caution must be exercised to ensure that studies are conceptually and methodologically sound [81,82].…”
Section: Neurophysiological Mechanismsmentioning
confidence: 74%
“…In addition to quantifying synchronized and symmetric brain-networks between brains, some dual-EEG studies have also shown asymmetric brain-coupling patterns between leader-follower participants of a dyad (Babiloni et al, 2007, Dumas et al, 2012, Sanger et al, 2012. This asymmetry has been reported either as functional connectivity (i.e.…”
Section: Introductionmentioning
confidence: 99%